Waterflood and Polymer Injection Design for New Target Reservoir based on Injection Pattern Optimization, Injection Rate Sensitivity, and Injection Pressure Sensitivity - Fransiscus Asisi Lugas Ariobimo; Swadesi, Boni; Suhascaryo, Nur (Journal of Petroleum and Geothermal Technology, 2025)
Field “X” is in Tabalong Regency, South Kalimantan, and is operated by Pertamina Hulu Indonesia Zona 9. The peak primary production occurred in March 1963, reaching 47,963 BOPD. Full-scale waterflood implementation with a staggered line-drive injection pattern began in January 1995, and the peak secondary production occurred in January 1999 at 10,095 BOPD. This study was conducted using a dynamic model that had undergone initialization validation and history matching. The assessment of polymer injection pattern candidates was carried out through a screening stage based on screening criteria and reservoir property analysis to determine patterns that could be prioritized as pilot areas for an optimal polymer injection scenario in Zone B. Pattern analysis criteria were based on movable remaining oil saturation, movable remaining oil in place, pattern area, and average transmissibility, evaluated for the Zone B reservoir under post-waterflood conditions. Sensitivity analyses on water injection rate and injection pressure were then performed to obtain the optimum waterflood injection scenario. After optimizing the injection pattern and determining the optimum waterflood injection scenario, polymer input parameters were applied to the model, followed by sensitivity analyses on polymer injection rate and pressure to obtain the optimum polymer injection scenario for Zone “B” of Field “X By the end of the production forecast in January 2066, the optimum waterflood injection scenario at the end of the production forecast provides an incremental oil gain of 1.5 MMSTB with an incremental recovery factor of 2.19% relative to OOIP, while the combination of optimum waterflood and polymer injection at the end of the production forecast provides an incremental oil gain of 2.14 MMSTB with an incremental recovery factor of 3.13% relative to OOIP; demonstrating improved sweep efficiency, oil bank formation, and effective mobilization of residual oil across Zone B.